Sunlight-driven photocatalytic mineralization of antibiotic chemical and selected enteric bacteria in water via zinc tungstate-imprinted kaolinite - Moses O. Alfred; Chidinma G. Olorunnisola; Temidayo T. Oyetunde; Peter Dare; Raquel R. C. Vilela; Andrea de Camargo; Nurudeen A. Oladoja; Martins O. Omorogie; Olumide D. Olukanni; Artur de Jesus Motheo; Emmanuel I. Unuabonah (Green Chemistry Letters and Reviews, 2022)
This study reports the synthesis of sunlight-active zinc oxide-tungstate-kaolinite photocatalytic composite prepared via a green process (solvent-free mechano-thermal process) at an optimum temperature of 500°C for 1 h in a furnace. Electron Paramagnetic Resonance (EPR) study suggests the presence of W5+ defect states in the prepared photocatalytic composite (ZnWK-5), which is responsible for its photoactivity in visible light. Results from further analysis show that hole (h+) and superoxide radical (.O2−) are the major contributors to the photocatalytic efficiency of ZnWK-5 photocatalytic composite. This photocatalytic composite was used to treat water containing an antibiotic chemical-ampicillin (AMP) under sunlight. Mass spectrometry analysis of the treated water suggests that the mechanism of photodegradation of AMP is via several bond and ring cleavages, including amide bond, phenyl ring, and β-lactam ring cleavages. These cleavage reactions were followed by subsequent mineralization of ca. 98% after 5 h without the formation of toxic products. The introduction of phosphate and carbonate anions had a serious negative impact on the photocatalytic activity of the composite. However, the photocatalytic composite completely disinfected water contaminated with gram-(−ve) and gram-(+ve) bacteria. Even after five re-use cycles, the photocatalytic composite maintained a 90% photodegradation efficiency of ampicillin in water.